Pemikiran Politik Perempuan Nahdlatul Ulama (NU) dalam Perspektif Feminisme: Penelusuran Pemikiran Mainstream dan Non-Mainstream - Linda Dwi Eriyanti (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
This study aims to identify the appropriate perspective to describe non-mainstream feminist political thought of NU women. The authors found that political thought of NU women were categorized into the mainstream and non-mainstream thinking. Thought mainstream covers many of the issues associated with formal politics of women, gender equality, as well as sexuality. Mainstream thinkers give prescriptions on such issue through formal state politics and in public areas. While the women's non-mainstream political thought, although identifying the source and impact of the oppression of women is equal to mainstream thinking, they leave notes and analysis of different approaches. This study attempts to framing NU diverse political thought throught the four schools of feminism, the liberal feminism, marxist feminism, socialist feminism and radical feminism. This study found that the ideas of radical feminism turned out to give space to the explanation of political thought NU women's non-mainstream, where they tend to emerge from the lower classes, and not formally organized.